2020
DOI: 10.6008/cbpc2179-6858.2020.004.0026
|View full text |Cite
|
Sign up to set email alerts
|

Ferramenta de programação neurolinguística para intermediação de conflitos ambientais

Abstract: Em uma era onde o desenvolvimento de um país muitas vezes está atrelado a implantação de grandes indústrias e empreendimentos, os impactos ambientais, positivos e negativos, aparecem e vem acompanhados de notórios conflitos. Devido a sua complexidade e importância, os estudos sobre esses conflitos ambientais tornaram-se relevantes e necessários nas últimas décadas. Muitas vezes os conflitos podem ser amenizados por processos de comunicação eficientes. A programação neuroliguistica (PNL) trás ferramenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since environmental licensing is a decision-making process concerning environmental resources, it can lead to different socio-environmental conflicts or bring pre-existing conflicts to light (BERNARDELLI JÚNIOR; RUIZ; GALLARDO, 2017;SOARES;OLIVEIRA;FONSECA, 2015;TORRES;GONÇALVES, 2019), since they derive from different environmental resource use and significance projects (ACSELRAD, 2004). On the other hand, previous studies have shown that conflicts can often be influenced by efficient communication processes (GHOZ et al, 2020), but it is essential having prior knowledge about the origins of the conflict, as well as about the conflict itself and about what is in dispute for communication to be effective. Therefore, it is necessary deeply understanding these issues in order to investigate the meaning given to the "environment" by each involved party.…”
Section: Introductionmentioning
confidence: 99%
“…Since environmental licensing is a decision-making process concerning environmental resources, it can lead to different socio-environmental conflicts or bring pre-existing conflicts to light (BERNARDELLI JÚNIOR; RUIZ; GALLARDO, 2017;SOARES;OLIVEIRA;FONSECA, 2015;TORRES;GONÇALVES, 2019), since they derive from different environmental resource use and significance projects (ACSELRAD, 2004). On the other hand, previous studies have shown that conflicts can often be influenced by efficient communication processes (GHOZ et al, 2020), but it is essential having prior knowledge about the origins of the conflict, as well as about the conflict itself and about what is in dispute for communication to be effective. Therefore, it is necessary deeply understanding these issues in order to investigate the meaning given to the "environment" by each involved party.…”
Section: Introductionmentioning
confidence: 99%